Development of Economics Teaching Materials Using Android-Based Mit App Software - Muh. Fahrurrozi; Mispandi Mispandi; Baiq Jauziati (IJE : Interdisciplinary Journal of Education, 2023)
The purpose of this research is to develop Android-based economic teaching materials using App Inventor Software. To find out the effectiveness of Android-based economic teaching materials using the App Inventor Software for student independence in learning. The method used in this research development is a modified Borg & Gall model with four steps of initial product development, design validation, product trials and validation. The results of the study showed that the validation of the material expert was workable with an average score of 84%. The assessment of the validator of the media expert is quite decent with an average score of 83.3%. After the validation process was carried out, then continued to a small group trial consisting of 5 students of class X by 92.2% and economics teachers. The results obtained are feasible with an average score of 95%. For field trials also received a decent rating of 88.1% of the responses of 15 students. 100% of teacher responses in economics. The development of Android-based economic teaching materials is declared feasible to improve student learning outcomes because the results of the classical completeness analysis is over 85% which is 93%.